The role of family caregivers in medication adherence of elderly in Asian setting: a scoping review - Wiedyaningsih, Chairun; Widyakusuma, Niken Nur; Sri Suryawati (Indonesian Journal of Pharmacology and Therapy, 2023)
Family caregivers for elderly play a very important role in implementing drug adherence, especially in Asian countries. Various determinants of medication adherence included caregivers as family support. Although the relationship between family support is not always significant, understanding the factors of family caregivers on medication adherence is important, especially when improving adherence in Asian countries. The following scoping review was conducted to provide an overview of caregivers, and its relationship to medication adherence in Asian settings. PRISMA-ScR guideline and checklist was used for the search process and to guide reporting. Review selection and characterization were performed by reviewers independently. In total, 22 papers were included in the review, published from 2011 to 2021. The studies varied in terms of purpose, methodology, and detail of reporting. Family caregiver is an important determinant of medication adherence, especially for areas where extended family culture is still strong, such as in Asia. Understanding the local culture, aspects of family burden and economic, as well as the role of the health profession, especially pharmacists in health services are needed to improve adherence. Therefore, further research with quality methods is needed.